Trans-ferulic acid valorization into stilbene derivatives via tandem decarboxylation/Heck coupling using Pd/Al-SBA-15 materials. (September 2022) - Maties, G.; Gonzalez-Arellano, C.; Luque, R.; Montejano-Nares, E.; Ivars-Barceló, F.; Pineda, A.
Abstract: Pd-containing Al-SBA-15 materials were prepared and characterized in view of their utilization in the two-step valorization of trans -ferulic acid into stilbenes via tandem decarboxylation/Mizoroki-Heck coupling. Materials were found to be highly active and selective in the proposed chemistries, with quantitative conversion to target products under mild reaction conditions (typically 100 °C, 3–6 h reaction). Relevant insights on catalyst deactivation via sintering (Pd nanoparticles agglomeration) were also observed for the synthesized materials. Highlights: Pd-containing Al-SBA-15 for trans -ferulic acid conversion into stilbenes. Tandem decarboxylation/Mizoroki-Heck coupling reactions. Quantitative conversion under mild reaction conditions. Relevant insights on catalyst deactivation via sintering and leaching.